Hubungan Dukungan Keluarga dengan Kualitas Hidup Lansia di Wilayah Kerja Puskesmas Kec. Manuju Kab. Gowa - Santi Santi; Fanny Dewi Sartika; Andi Budiyanto Adi Putra (Fatiakara Care: Jurnal Ilmiah Keperawatan, 2025)
Family support can provide a person with a sense of physical and psychological security through their attitudes, actions and acceptance. Family support greatly influences the quality of life of the elderly. The quality of life of the elderly can be the elderly's feelings about their well-being over time, including physical health, psychological health, social and environmental health. The aim of this research is to analyze the relationship between family support and the quality of life of elderly people in the work area of the District Health Center. Manuju District. Gowa 2024. The research method used is a correlation research design with a cross sectional approach. Sampling technique using simple random sampling technique with a total of 62 respondents. The research results show that the majority of family support is 47 people (75.81%) and the majority's quality of life is adequate for 34 people (54.84%). Chi square test with a p value of 0.02 (p<0.05). It can be concluded that there is a relationship between family support and the quality of life of the elderly. It is hoped that families can maintain and improve personal/social relationships among the elderly so that family support and quality of life for the elderly are in the good category.